PENGARUH KUALITAS PELAYANAN, HARGA DAN PROMOSI TERHADAP KEPUASAN KONSUMEN (STUDY KASUS PADA DISTRO ANTIVIRUS BOYOLALI) - Aditya Wahyu Prasetyo; Listyowati Puji Rahayu; Hari Purwanto (EKOBIS, 2023)
ABSTRACT This study aims to determine whether service quality, price and promotion affect consumer satisfaction at the Boyolali Antivirus distribution. The population in this study are consumers who make purchases at the Boyolali Antivirus distribution. Data collection techniques by distributing questionnaires with a sample of 100 respondents. The research method is a quantitative method. Testing of data instruments was carried out with validity and reliability tests, for data analysis used normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, and hypothesis testing to determine whether the variables have a significant relationship. The results of this study are based on the results of the t test and the service quality variable 0.248 < t table 1.984 and the value of sig 0.804 > sig 0.05 which means that it is not significant, then Ho is accepted and Ha is rejected. This shows that the service quality variable partially has no effect on customer satisfaction, in other words the service quality variable has no significant effect on customer satisfaction, sig 0.00 t-table has a value of 1.984, and sig 0.000 sig 0.05 means significant, Ho rejected and Ha accepted. This shows that the promotion variable has a partial effect on consumer satisfaction, namely the promotion variable has a large effect on consumer satisfaction. Based on the results of the F test Sig.0,000<0,000. 0.05 means that all variables act simultaneously. By using a level (alpha) of 0.05 or 5%, Ho was successfully rejected and Ha was not. The rejection of Ho is evidenced by the calculation of the Sig value which can be concluded. Based on the acceptance test, we found the Rsqure value to be 0.88. This shows that the variables of service quality, price, and advertising together can explain 88% of consumer satisfaction variables, and the remaining 12%. With variables other than above. studied. Keywords : Quality of Service, Price, promotion and Customer Satisfaction